2015
DOI: 10.1111/jgs.13433
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Age‐Related Increases in Arterial Stiffness in Japanese and American Women

Abstract: Japanese women had smaller increases in central arterial stiffness with advancing age than U.S. women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Comparing our findings with previous studies, we found that baPWV among men in Beijing is higher than among Japanese and American males of the same age. Among the women in our study, baPWV was higher than in Japan and closer to values in the United State [ 36 ]. We surmise that these differences relate mainly to lifestyle differences, but in the absence of original data, this can only be confirmed by experiments with larger samples.…”
Section: Discussionsupporting
confidence: 62%
“…Comparing our findings with previous studies, we found that baPWV among men in Beijing is higher than among Japanese and American males of the same age. Among the women in our study, baPWV was higher than in Japan and closer to values in the United State [ 36 ]. We surmise that these differences relate mainly to lifestyle differences, but in the absence of original data, this can only be confirmed by experiments with larger samples.…”
Section: Discussionsupporting
confidence: 62%
“…Arterial stiffness also increases with age. (10) Japan is a super-aging society, and controlling the increase in arterial stiffness during acute hyperglycemia in the elderly is considered important.…”
mentioning
confidence: 99%
“…Although there were fewer participants in the oldest age group in our study, the addition of participants up to the age of 85þ years adds significantly to the existing knowledge along with the analysis of health and high risk groups. In contrast, a study comparing healthy Japanese and US adults found that there were similar rates of aging between the two counties, except for females, where Japanese females exhibited slower arterial stiffening [26]. However, this study only went up to the age of 69 years using carotid-femoral and brachial-ankle PWV and did not address the impact of cardiovascular risk factors.…”
Section: Geographic Differences In Arterial Stiffnessmentioning
confidence: 87%